Морозостійкість магнолій та льодоутворення у тканинах пагонів - Палагеча, Р.М.; Китаєв, О.І.; Таран, Н.Ю. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Методом дифференционного термического анализа (ДТА) проанализирован процесс образования льда в коре и древесине побегов нескольких контрастных по морозостойкости видов рода Magnolia. Установлено, что амплитуды экзотермического процесса для морозостойких видов (M. kobus, M. salicifolia) значительно отличаются в разных тканях и являются большими на 2-3° С, чем для менее устойчивых видов (M. liliflora, M. denudata, M. x soulangiana). ДТА ледообразования очень четко и показательно определяет особенности реакции растений на неблагоприятное влияние изменчивых температур в зимний период и может быть использован, как показатель морозостойкости растений. The process of ice formation in bark and wood of shoots contrasting in frost resistance of some species of the genus Magnolia by method of differential thermal analysis (DTA) has been analysed. It has been established, that the amplitudes of exothermic process for the frost resistant species (M. ko-bus, M. salicifolia) differ greatly by nature of ice formation in different tissues and are 2—3 °C higher than less resistant species (M. liliflora, M. denudata, M. x soulangiana). DTA of ice formation determines very clear and demonstrative a plant reaction on unfavorable influence of changeable temperatures in winter period and may be used as an index of plant frost resistance.